Expectations Set High : Understanding Reservation Wages in North Macedonia - Petreski, Marjan (World Bank, Washington, DC, 2019)
The objectives of this study are to understand the determinants of reservation wages and measure the gap between reservation and market wages in North Macedonia. The study makes use of recently collected information on reservation wages in the Labor Force Survey 2016 and 2017. The analysis relies on ordinary least squares, propensity score matching, Heckman-corrected estimates, and panel fixed effects. The results suggest that it is mainly supply factors that shape reservation wages in the country. Higher education achievement sizably increases future wage expectations, while age and longer spells of unemployment reduce them. Demand factors are found to be insignificant for reservation wage formation. Observed by skill level, the results suggest that low-skilled individuals consistently value their skills higher than what the market offers and set too high expectations. These circumstances are aggravated in cases where the household is well-off and/or receives remittances. By contrast, highly skilled individuals, despite maintaining a positive reservation wage gap, have a propensity to accept market wages even when they fall below their reservation wage, likely because these workers fear rapid depreciation of their skills.